Professional Teacher Identity on the Boundary: Student Study Group Facilitators Negotiating Their Identity - David R. Arendale; Amanda R. Hane (MDPI AG, 2023)
This study focuses on undergraduate student paraprofessionals who facilitated peer study groups for academically challenging college courses. A grounded qualitative research study of these student facilitators at an institution identified their professional identity development in unexpected ways that went against written policies for teacher attitudes and behaviors. Rather than perceiving themselves as peer study group facilitators following a narrow job description, many of them referred to themselves as teachers and acted accordingly, breaking the boundaries of behavior established by the study group program administrator. This article unmasks this professional identity emergence, postulates the mechanism for this choice, presents a model to explain it, and makes recommendations for talking openly about this identity and the subsequent behaviors that occurred as a result by the facilitators and the implications for the PAL program.